Patient satisfaction with procedural sedation in the emergency department. (29th March 2017) - Johnson, Olivia G; Taylor, David McD; Lee, Marina; Ding, Juen‐Li; Ashok, Aadith; Johnson, Damian; Peck, Daniel; Knott, Jonathan; Weinberg, Laurence
Abstract: Objective: The aim of this study was to determine patient satisfaction with procedural sedation as a function of nature of the procedure and depth of sedation. Method: We undertook a prospective observational study of adult patients who received procedural sedation in two EDs (20 month period). The level of sedation was determined by an investigator, using the Observers Assessment of Anaesthesia/Sedation Scale (1 = awake to 6 = no response to noxious stimuli). Patient satisfaction was measured with the Iowa Satisfaction with Anaesthesia Scale after full recovery. This was self‐administered, comprised 11 items (e.g. 'I felt pain') and has a score range of −3 (poor satisfaction) to +3 (very satisfied). Results: A total of 163 patients were enrolled (51.2% men, mean age 50.7 years). The median (interquartile range) satisfaction score was 2.7 (0.7). Patient satisfaction was lower among patients who had orthopaedic procedures (median 2.6 vs 2.8, P < 0.01) and among patients who had a pre‐sedation opioid (2.6 vs 2.8, P = 0.03). Satisfaction was positively correlated with deeper sedation (Spearman's correlation coefficient 0.49, P < 0.001). Satisfaction also differed significantly between the four most common sedation regimens ( P < 0.001). It was greatest among those who were administered propofol with or without fentanyl and least among those who were administered nitrous oxide with or without opioid. Patients sedated with propofol with or without fentanyl had the greatest depths of sedation. There was no difference in satisfaction among patients who were and were not sedated by a consultant (median 2.6 and 2.7, respectively, P = 0.84). Conclusion: Generally, the level of patient satisfaction is high. Greater satisfaction is associated with deeper sedation, sedation with propofol and non‐orthopaedic procedures.